Obesity: Lifestyle management, bariatric surgery, drugs, and the therapeutic exploitation of gut hormones. Issue 5 (August 2015) - Behary, Preeshila; Cegla, Jaimini; Tan, Tricia M.; Bloom, Stephen R.
Abstract: Obesity is on the rise and the pursuit of efficient and safe treatment is ongoing. Available anti-obesity medical therapies have so far proved to be disappointing, whereas bariatric surgery is leading the way and offers long-term health benefits. Part of the success of bariatric surgery is thought to be mediated by gut hormones. A better understanding of the role of gut hormones within the gut-brain signaling pathway in the control of hunger, satiety, and energy homeostasis, has led to their therapeutic exploitation as possible anti-obesity drugs. In this review, we provide a summary of currently available treatment options for obesity from simple lifestyle modifications and bariatric surgery to traditional and novel medical therapies.